Improvement of Learning Outcomes Through STAD Type Cooperative Learning in Indonesian Learning - Kasmawati Kasmawati (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
This study aims to improve student learning outcomes through cooperative learning strategies of the Student Team Achievement Division (STAD) at SMA Negeri 6 Maros. This type of research is classroom action research (CAR) which consists of planning, action, observation, and reflection. The subjects of the study were students of class XI MIPA. Data collection techniques use daily replay documentation to show improvement. The data were analyzed with descriptive statistics. The learning outcomes Indonesian class XI MIPA 3 students at SMA Negeri 6 Maros who were taught using the STAD (Student Team Achievement Divisons) type cooperative learning model were classified as very high with an average score of 95.15% of 25 students. This shows that cooperative learning strategies with STAD can improve student learning outcomes.